Telecentres and the provision of community based access to electronic information in everyday life in the UK - Debbie Ellen (Information Research: An International Electronic Journal)
This paper presents research undertaken for a PhD between 1997 and 2000 in the United Kingdom. The study explored three themes, the use of electronic information in everyday life, the use of telecentres by local communities in everyday life and community involvement strategies in the design, development and implementation of telecentres. Results led to development of a framework to inform future community based ICT initiatives. The findings and methods used to analyse the data are relevant to both future study of community based ICT initiatives and the broader areas of information seeking, information seeking behaviour and user needs. Consequently, it is hoped they will be used by other researchers wishing to take a qualitative approach when studying in these areas. This paper will report findings relating to the use of electronic information in everyday life, setting these findings within the context of the whole study. The full PhD thesis is available on-line.